Mechanistic investigation of aziridine aldehyde-driven peptide macrocyclization: the imidoanhydride pathway1. Issue 10 (14th October 2015) - Zaretsky, Serge; Hickey, Jennifer L.; Tan, Joanne; Pichugin, Dmitry; St. Denis, Megan A.; Ler, Spencer; Chung, Benjamin K. W.; Scully, Conor C. G.; Yudin, Andrei K.
<x xml:space="preserve">Abstract</x> Aziridine aldehydes participate in a multicomponent reaction with α-amino amides and isocyanides to generate reactive imidoanhydride intermediates.